2003
DOI: 10.1210/jc.2003-030211
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Main Action on the Regulation of Growth Hormone Release Is Exerted at Hypothalamic Level

Abstract: Ghrelin, a recently isolated hormone, seems to participate in the physiological regulation of GH secretion. Exogenously administered ghrelin stimulates GH discharge in all species so far tested including man, but whether this action is exerted at pituitary or alternatively at hypothalamic level is not known at present. To understand the point of ghrelin action a group of patients with organic lesion mainly in the hypothalamic area and matched controls were studied. Patients showed a severe GH deficiency after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0
11

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 0 publications
7
68
0
11
Order By: Relevance
“…We and others have shown that GHS retain their GH-releasing effect in active acromegaly (19). Ghrelin, the natural ligand of the GHS-R with more potent GH-releasing activity and specificity was found to elicit an increase in GH in newly diagnosed acromegalic patients, and the response was positively correlated with basal IGF-I concentrations (20,21).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…We and others have shown that GHS retain their GH-releasing effect in active acromegaly (19). Ghrelin, the natural ligand of the GHS-R with more potent GH-releasing activity and specificity was found to elicit an increase in GH in newly diagnosed acromegalic patients, and the response was positively correlated with basal IGF-I concentrations (20,21).…”
Section: Discussionmentioning
confidence: 84%
“…bolus). This dose of ghrelin has previously been shown to be effective in stimulating GH release in humans (20). Samples for GH were taken at 0, 15, 30 and 45 min after ghrelin administration.…”
Section: The Ghrelin Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The GH response to ghrelin is partially inhibited by GHRH receptor antagonists and disruption of communication between the hypothalamus and pituitary gland, 75,76 supporting the assumption that the effect of ghrelin on GH secretion is primarily mediated by GHRH-secreting neurons at the level of thehypothalamus. 21,74,76,77 In anesthetized rats, ghrelin administered IV stimulates GH release without affecting secretion of other adenohypophyseal hormones.…”
Section: 74mentioning
confidence: 75%
“…21,74,76,77 In anesthetized rats, ghrelin administered IV stimulates GH release without affecting secretion of other adenohypophyseal hormones. 8 Also, in cultured rat pituitary cells, ghrelin stimulates GH release in a dosedependent manner without affecting the release of other pituitary hormones, even at high concentrations.…”
Section: 74mentioning
confidence: 99%